Picturing the social landscape : visual methods in the sociological imagination - Knowles, Caroline, 1954-; Sweetman, Paul (Routledge, 2004)
In this collection international experts explain how they have used visual methods in their own research, examine their advantages and limitations, and show how they have been used alongside other research techniques.